Anticoagulant drugs for patients with atrial fibrillation on dialysis: a systematic analysis and network meta-analysis - Shen, Xian-Feng; Zhang, Chao; Hu, Jun; Zhang, Tao; Ma, Bin (Frontiers in Pharmacology, 2023)
Objective: There remains a lack of clarity regarding the efficacy and risks associated with direct oral anticoagulants (DOACs) in end-stage renal disease (ESRD) patients with atrial fibrillation (AF) undergoing dialysis, primarily due to limited retrospective studies. Therefore, the objective of this study was to evaluate the existing data to propose a practical protocol for the clinical utilization of DOACs in ESRD patients with AF undergoing dialysis. Method: PubMed, EMBASE and Cochrane Central Register of Controlled Trials (Central) were searched for clinical studies evaluating DOACs in ESRD patients with AF on dialysis published up to February 2, 2023. The DOACs included warfarin, dabigatran, apixaban, edoxaban, and rivaroxaban. The outcomes were mortality, ischaemic stroke, haemorrhagic stroke, any stroke, gastrointestinal bleeding, major bleeding, intracranial bleeding, and minor bleeding. Results: Compared with placebo, apixaban (HR=0.97, 95%CI: 0.88 to 1.07), rivaroxaban (HR=0.91, 95%CI: 0.76 to 1.10), and warfarin (HR=0.96, 95%CI: 0.90 to 1.01) did not reduce mortality. Regarding direct comparisons of mortality, the comparisons of warfarin vs. apixaban (HR=0.99, 95%CI: 0.92 to 1.06), placebo vs. warfarin (HR=1.04, 95%CI: 0.99 to 1.11), and rivaroxaban vs. warfarin (HR=0.96, 95%CI: 0.80 to 1.14) did not significantly reduce mortality. Based on the SUCRA, rivaroxaban (75.53%), warfarin (62.14%), and apixaban (45.6%) were the most effective interventions for managing mortality, and placebo (16.74%) was the worst. Conclusion: In conclusion, rivaroxaban demonstrated efficacy in reducing mortality and the incidence of ischaemic stroke, gastrointestinal bleeding, and intracranial haemorrhage. Dabigatran is recommended for the prevention of haemorrhagic stroke. However, caution should be exercised due to the risk of major bleeding. Warfarin can effectively reduce minor bleeding but does not offer significant protection against gastrointestinal or intracranial bleeding. Apixaban was not recommended for mortality reduction or for preventing ischaemic or haemorrhagic strokes. Further research will be warranted to establish specific clinical protocols.